Preparation and characterisation of microencapsulated paraffin wax with polyaniline-based polymer shells for thermal energy storage - Silakhori M.; Metselaar H.S.C.; Mahlia T.M.I.; Fauzi H. (Maney Publishing, 2023)
Microencapsulated paraffin wax with polyaniline shells is synthesised as thermal energy storage material by in situ polymerisation. Paraffin wax is the core material and polyaniline is the shell in this preparation. These materials are environment-friendly. The chemical structure, surface morphologies, thermal properties and thermal stability of the encapsulated paraffin wax are determined by Fourier transform infrared spectrophotometry, field-emission scanning electron microscopy, differential scanning calorimeter and thermogravimetry analysis, respectively. The field-emission scanning electron microscopic results indicate that the paraffin wax is encapsulated well and that the capsules are spherical in shape. The differential scanning calorimetric analysis shows that the encapsulated paraffin wax has a large energy storage and releases capacity (22-121 J g-1) depending on the different ratios of the paraffin wax and polyaniline. The thermogravimetric analysis results indicate that polyaniline can improve the thermal stability of encapsulated paraffin wax because of the synergistic effect between the two (paraffin wax and polyaniline). Based on these results, it can be concluded that the microencapsulated paraffin wax that acts as a microencapsulated phase change material has a good potential for thermal energy storage purposes. © 2014 W. S. Maney & Son Ltd.